„Kobieta, która zatraciła człowieczeństwo” – sprawa Pauline Nyiramasuhuko - Spychalska, Aleksandra (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2015)
This article presents the case of Pauline Nyiramasuhuko – Rwandan Minister for Family Welfare and the Advancement of Women – who was tried at the International Criminal Tribunal for Rwanda for genocide, public and direct incitement to commit genocide, crimes against humanity, and war crimes. The trial of Nyiramasuhuko was unprecedented. It was the longest and most expensive trial the ICTR has ever held. It was also the first trial before an international criminal court in which the accused was a woman. Furthermore, among the charges that were brought against her – for which she was sentenced in the first instance to life imprisonment – was rape as a crime against humanity
Keywords: ICTR; International Criminal Tribunal for Rwanda; Rwanda